The Influence of Pregnant Women Classes on Knowledge, Attitudes and Skills of Conducting Early Detection of Danger Signs during the Second Trimester of Pregnancy in Buleleng Regency - Desak Ketut Sugiartini (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Efforts need to be made to improve the implementation of pregnancy for pregnant women, one of which is to increase information and knowledge of mothers, attitudes and family support for the knowledge, attitudes and skills of Early Detection of Danger Signs during the Second Trimester of Pregnancy. This study aimed to determine the influence of pregnant women classes on knowledge, attitudes, and early detection of danger signs during trimester II pregnancy in the Buleleng Regency. The research method used observational research with a cross-sectional approach. The population in this study were pregnant women who carried out pregnant women and visited at least 4 times as many as 124 mothers. Sampling was done by purposive sampling with a sample size of 82 pregnant women in TM II. The research instrument used a questionnaire with closed questions that had been validated and reliable was 0.6. The study was conducted at the Community Health Center in Singaraja City. Analysis of the data used in this study is the Logistic Regression statistical test with α 0.05. The results of the study have a significant effect on the class of pregnant women on the knowledge of the p value of 0.027, there is no significant effect of the class of pregnant women on the attitude of the p value of 0.347 and there is a significant influence on the class of pregnant women on the skills of pregnant women about the danger signs of TM II pregnancy p value of 0.008. Conclusion there is the influence of the class of pregnant women on maternal knowledge and there is no effect of the class of pregnant women on the attitude of mothers to recognize the danger signs of pregnancy, there is the influence of classes of pregnant women on the skills of mothers to recognize the danger signs of pregnancy